Emotional Intelligence and Transformational Leadership Traits Among Licensed Certified Public Accountants Located in the United States - Charles, Sabine; Walker, Andress; Hillstead, Coy; Domingo, Aldwin (Advances in Social Sciences Research Journal, 2023)
This current research study examined if there is a linear relationship between various Emotional Intelligence traits and Transformational Leadership Traits among a sample of 104 licensed Certified Public Accountants (CPA) located in the United States who are currently not in workplace leadership positions. This research is appropriate for CPA professionals because CPA professionals must evaluate different points of view, conduct an effective analysis of accounting data, and embrace the highest ethical standards as part of their professional duties. Moreover, Transformational Leadership traits (Avolio & Bass 2004) fit nicely within Peter Salovey and John Mayer’s (1990) elements of Emotional Intelligence. Overall, the research study did find evidence for positive linear relationships between the predictor variables of Emotional Intelligence traits of Managing Their Own Self-Relevant Emotions and Managing Others’ Emotions among licensed Certified Public Accountants (CPA) and the dependent variables of Transformational Leadership Traits related to Idealized Attributes, Inspirational Motivation, Intellectual Stimulation, and Individualized Consideration. The researchers recommend that any future professional development among Certified Public Accountants (CPA) who aspire to seek out workplace leadership positions needs to be focused on the cornerstones of Managing Their Own Self-Relevant Emotions and Managing Others’ Emotions.